Why Did You Become a Police Officer? Entry-Related Motives and Concerns of Women and Men in Policing - Clinkinbeard, Samantha S. (Criminal justice and behavior, 2021)
As police agencies in the United States suffer declining applications and struggle to recruit women, the National Institute of Justice has identified workforce development as a priority research area. To recruit more effectively, we must understand what attracts people to policing and what deters them. We surveyed officers in two Midwestern police departments (n = 832) about entry motivations and concerns and examined gender differences. Serve/protect motivations were most important for men and women, though women rated the category significantly higher. Women and non-White officers rated legacy motives higher than did males and White officers. Women reported more concerns overall and scored higher on job demands and acceptance concerns; officers of color also reported more acceptance concerns than White officers. The largest gender differences were associated with gender-related obstacles and stereotypes (e.g., discrimination; being taken seriously; physical demands), indicating recruitment reform necessarily includes improving systemic issues.